Dunmore Augustinian Friary, exterior west wall, door, capital frieze - O'Donovan, Danielle (My University, 2008)
Capital frieze running the length of the splayed door jamb. Moulding comprises, from centre: central frontal roll-and-fillet flanked above and below by fillet, hollow, and scroll.
Door
Keywords: scroll; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Gothic doorways; Architecture, Augustinian; Late Medieval; roll-and-fillet moldings; moldings, hollow; fillets (moldings)